Isolation of mesenchymal stem cells and their participation in the modulation of the immune response - Bustos-Araya, Salomé (2018)
Mesenchymal stem cells (MSC) are a type of spindle-shaped pluripotent cells with the ability to differentiate into chondrocytes, osteocytes, and adipocytes, among others. These cells can be obtained from bone marrow, adipose tissue or umbilical cord blood; this fact has allowed to study its structural and functional properties. Although bone marrow has been the main source of MSC, it has been found that there are aspects that hinder its use, including a limited growth rate, variation in the capacity to differentiate according to the bone marrow donor´s age, and risk in the sampling procedure. Therefore, studies in adipose tissue and umbilical cord blood have increased, as well as in methods currently used for the extraction of MSC from all sources. Currently, these cells are known to have a high immunomodulatory capacity; for that reason, this has generated several preclinical and clinical studies for their possible use as treatment in people with autoimmune diseases and graft-versus-host disease in transplant patients.